Estudio de prefactibilidad para la instalación de una planta de jugo concentrado de maracuyá (Passiflora edulis) en envase bag-in-box - Añaños Marquez, Yomira Olga (2020)
The research aims to install a passion fruit juice concentrate in a bag-in-box container plant to meet local demand. Passion fruit has always been present in the Peruvian daily diet for its pleasant flavor; in addition to its great nutritional value. Therefore, the product of this research is proposed as a healthy alternative to combat the problem of overweight in Peru. To guarantee this value offer, aseptic filling will be used as a packaging technology that increases perishability and avoids the use of preservatives. In the first chapter the problem of the project, objectives, hypotheses, justification, sources of research to be used will be evaluated; as well as the referential and conceptual framework. In the second chapter, through the analysis and use of primary and secondary tools, our target market will be segmented and defined. In the third chapter, using the qualitative and quantitative method, the location of the plant will be defined. Regarding the fourth chapter, the different plant size relationships will be evaluated to subsequently select the appropriate plant size. In the fifth chapter, the project engineering will be detailed, emphasizing aspects that cover the production process, plant capacity and distribution, requirements of raw material, machinery and personnel, quality management and the environment, among others. In the sixth chapter, the organization chart of the company will be structured. In the seventh chapter, the required investment will be quantified by estimating the required assets and working capital. Likewise, income and expenses will be budgeted. In addition, the project will be evaluated from an economic and financial perspective using indicators such as VAN, TIR, R B / C and PR, together with the main ratios and a sensitivity analysis. In the last chapter, a social evaluation of the project will be carried out; through different indicators.